KESETARAAN GENDER DALAM PENDIDIKAN ISLAM (Studi Pemikiran Pendidikan Hamka dalam Tafsir al-Azhar) - Juono, Ribut Purwo (Universitas Islam Negeri Raden Intan Lampung, 2015)
GENDER EQUALITY IN ISLAMIC EDUCATION (Study on Hamka’s Educational Thought in His Tafsir al-Azhar): The research entitled of equality of gender in Islamic education has represent about idea studying that try to express some problems related to equality of gender at scope in Islamic education, specially the Islamic education ideas of one of the modern Indonesia mufassir, Hamka. Target desired or like to achieved from this research is describing Hamka’s education ideas based on equality of the gender perspective. Besides, this research proposed also for understand the interpretation methodology used by Hamka and it’s corelation with his ideas about Islamic education in gender perspective. This research explain also about relevance of his ideas for the developing of national education system. The result of research is statement that the theme of gender equality has not found in Hamka’s education ideas, but researcher can make conclusion that in general, Hamka’s education ideas has free from misogynist and discriminative opinion to the woman.